Physics & chemistry of fullerenes : a reprint collection - Stephens, Peter W. (Advanced series in fullerenes, 1993)
The creation of the hollow carbon buckminsterfullerene molecule as well as methods to produce and purify bulk quantities of it has triggered an explosive growth of research in the field. Superconducting and magnetic fullerides, atoms trapped inside the fullerene cage, chemically bonded fullerene complexes, and nanometer-scale helical carbon tubes are some of the leading areas that have generated much excitement. This book is intended as a guide to the literature for the scientist who is just entering fullerene research, and will be one more valuable volume to the collection for the established worker. It contains reprints of some sixty most important research papers, with focus especially on those papers that have guided further work in the field. There is also a short review of the field, with references to many other publications.